Effect Of Arsenic On The Nutrient Uptake Pattern Of Amaranthus (Dhaka University Journal of Biological Sciences, 2012)
A macrocosm study was carried out to assess the transfer of arsenic (As) from irrigation water and sludge of arsenic removal water filter to two varieties of Amaranthus and their effects on phosphorus (P), potassium (K), sulfur (S), calcium (Ca) and magnesium (Mg) uptake. P and K uptake in shoot and root were negatively affected by As that were not significant. However, a significant negative relationship was observed between As and S in shoot. A positive and significant relationship existed between As and Ca of green Amaranthus shoot but it was negative and insignificant in case of red Amaranthus. Mg content of shoot and root was positively affected by As in green Amaranthus. On the other hand, in the red Amaranthus the relation between As and Mg was positive in the shoot but negative in the root. DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9748 DUJBS 2012 21(1): 87-96